(untitled) - Lucier, Thomas J. (New Jersey, 2006)
n The No-Nonsense Real Estate Investor’s Kit, noted author and real estate expert, Thomas J. Lucier provides detailed information, step-by-step instructions and practical advice for both beginning and experienced investors, who want to join the ranks of America's real estate millionaires!
Keywords: Real estate investment,Real property,House buying,House selling,Đầu tư bất động sản,Bất động sản,Bán nhà ở; Purchasing; United States,United States,United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ